SELECTING A PROCESS FOR OIL AND GAS DEVELOPMENT RESERVE DEPOSITS HYDROCARBONS - Abdirazakov Akmal Ibrahimovich; Mavlanov Zafar Alanazarovich (Web of Journals Publishing, 2024)
This article presents information on the need to introduce clarifying elements to create models of heterogeneous geological objects that have a significant impact on the parameters of cone process calculations.
Keywords: design, development, deposits, effect, hydrocarbons, hydrocarbons, model, production.